The expectation requirement prospective in fulfill industries needs in technical skills among vocational students (TVET). - Maselan, Norafiz; Ali, Maselan; Sufahani, Suliadi Firdaus (Universiti Teknologi Malaysia, 2017)
The investigation of the research is based on the expectation prospective requirement that’s needs to acquire among vocational students in University Tun Hussein On Malaysia (UTHM) The main objective is to observe the prospective students and establishment of foundation understanding that they need to fulfill the expectation of the industries. This is to ensure that they are well preparing in workplace in the future time. To achieve this by doing so is by implementation of phenomenological research method .From the experimental procedure is base from students prospective and by conducting questionnaire and interview. From these results, it can be conclude that students need more influence of self-establishment as they need to be ready entering in the industries of vocational.